Environmental changes of the last 1000 years on Prince of Wales Island, Nunavut, Canada. Issue 1 (1st January 2019) - Tamo, Camille; Gajewski, K.
ABSTRACT: A pollen record from a lake sediment core from southeastern Prince of Wales Island, Nunavut, Canada (SW08; 72.3177, −97.2678, 104 m a.s.l) provides the first high-resolution July temperature reconstruction for the last 1, 000 years for the central Canadian Arctic Archipelago. The vegetation underwent marked transitions during the Little Ice Age (LIA; 1500–1800 CE) and Medieval Climate Anomaly (MCA; 1090–1250 CE), which was primarily observed in the proportion of Cyperaceae, Poaceae, and Salix pollen. Cyperaceae pollen was highest in the samples corresponding to the MCA, whereas Poaceae increased during the LIA. In the last 30 years, Salix and Betula pollen increased. The mean July temperature reconstruction showed a long-term cooling from 1080–1915 CE with a sustained cold period from 1800–1915 CE prior to twentieth-century warming. A synthesis of paleoclimate records from across the Arctic demonstrates that pollen-based reconstructions record both high and low frequency climate variability, when sampling resolution is sufficient, and can improve regional climate reconstructions.